Zinc-Based Mineral (ZnSO4·7H2O) and Chelated (Zn-EDTA) Fertilizers improve the Productivity, Quality and Efficiency Indices of Field Pea (Pisum sativum L.) through Biofortification - Salwinder Singh Dhaliwal; Vivek Sharma; Arvind Kumar Shukla; Janpriya Kaur; Vibha Verma; Manmeet Kaur; Prabhjot Singh; Ahmed Gaber; Akbar Hossain (Journal of Trace Elements and Minerals, 2022)
Background: Field pea (Pisum sativum L.) is an essential pulse crop which can offer highly nutritional food to human beings. But, the inadequate availability of nutrients such as Zn could pose a significant threat to public health. Thus, there is a need to improve the food quality parameters and nutrient levels of the crop using biofortification thus, making it beneficial for human consumption. Methods: This study evaluated the influence of zinc (Zn) foliar application on food quality parameters, yield, Zn concentration and its uptake along with the economics of field pea cultivation. In the experiment, different concentrations of ZnSO4·7H2O and Zn-EDTA at the flowering and bud initiation stage were applied to the field pea. Results: The foliar application of ZnSO4·7H2O (1.0%) at the flowering and bud initiation stages (treatment T7) was highly efficient in increasing food quality parameters such as crude fibre, TSS, N, K and protein content with maximum values of 3.02, 20.5, 3.15, 3.41 and 14.97%, respectively. Also, the maximum yields of grain and straw in field pea for treatment T7 were 4840 kg ha−1 and 3275 kg ha−1, respectively. Similarly, the maximum Zn concentration in grain (54.8 mg kg−1) and straw (52.5 mg kg−1) of field pea was observed in treatment T7. Additionally, Zn uptake by grain (214 g ha−1) and straw (167 g ha−1) was the maximum for the treatment T7 involving ZnSO4·7H2O (1.0%). Whereas, grain Zn concentration and uptake decreased in the treatments involving the use of Zn-EDTA due to the formation of the complex resulting in the reduced availability of Zn to crop. Conclusion: Therefore, the application of ZnSO4·7H2O (1.0%) at the flowering and bud initiation stage significantly improved the food quality parameters, grain and straw yield, concentration of Zn and uptake over control and could be used to alleviate the Zn deficiency in field pea.